Production of UV-light-detectable faeces from house mice (Mus musculus domesticus) after consumption of encapsulated fluorescent pigment in monitoring bait - Frynta, Daniel; Kaftanová, Barbora; Fraňková, M; Aulický, Radek; Rödl, Pavel; Stejskal, Václav (Pest management science, 2012)
BACKGROUND: The authors investigated whether fluorescent pigment in thermoset melamine microcapsules incorporated into monitoring baits would be excreted in the faeces of wild house mice in a quantity and intensity that would be detectable by a human observer. RESULTS: Experimental mice produced 24-116 UV-visible faecal pellets per 24 h; the mean dry weight was 582 mg. The number and weight of the faeces was independent of mouse sex and weight. The defecation of UV-visible faeces began at 2-3 h, peaked at 5-8 h and was complete at 17 h after bait ingestion. The detectability of the highly fluorescent faecal pellets using a small UV flashlight approached 100%, and no false positives were recorded. CONCLUSION: The tested formulation is of significant value for rodent pest monitoring because faeces that are highly visible by UV light are produced for 15 h by mice after ingestion, and their detection is easy and unambiguous.
Keywords: přijímání potravy; Animals; deratizace; Eating; Female; Fluorescent Dyes; zvířata; feces; mužské pohlaví; Feces; Male; Mice; Rodent Control; Ultraviolet Rays; fluorescenční barviva; ženské pohlaví; ultrafialové záření; myši